2021
DOI: 10.1080/21655979.2021.2011636
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of DEAD-box helicase 21 (DDX21) inhibits proliferation, cell cycle, and tumor growth in colorectal cancer via targeting cell division cycle 5-like (CDC5L)

Abstract: Identification of novel anti-tumor target is crucial for cancer diagnosis, prognosis, and therapeutic strategy. The study aimed to explore the roles and interaction of DEAD-box helicase 21 (DDX21) and cell division cycle 5-like (CDC5L) in colorectal cancer (CRC) progression. Levels of DDX21 and CDC5L were detected in colorectal cancer cell lines by RT-qPCR and Western blot assay. The role of DDX21 and CDC5L on the cell proliferation, cell cycle and tumor growth were evaluated both in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Survival analysis showed that DDX56 was strongly associated with poor prognosis and that DDX56 was overexpressed in most tumor types. 61,62 We then focused on the significance of DDX56 at LIHC and further confirmed the high expression of DDX56 in 2 independent datasets and obtained consistent results at the protein level. Several studies have indicated that DDX56 interacts with the mitotic regulator serine/threonine phosphoprotein phosphatase (PP) 1 and the oncoprotein DEK to regulate tumor progression, and its high expression has been reported in breast and colorectal cancers.…”
supporting
confidence: 54%
“…Survival analysis showed that DDX56 was strongly associated with poor prognosis and that DDX56 was overexpressed in most tumor types. 61,62 We then focused on the significance of DDX56 at LIHC and further confirmed the high expression of DDX56 in 2 independent datasets and obtained consistent results at the protein level. Several studies have indicated that DDX56 interacts with the mitotic regulator serine/threonine phosphoprotein phosphatase (PP) 1 and the oncoprotein DEK to regulate tumor progression, and its high expression has been reported in breast and colorectal cancers.…”
supporting
confidence: 54%
“…1K , S1K, L ). Previous results showed that loss of DDX21 expression suppressed the CRC cell proliferation, cell cycle and tumor growth [ 29 , 30 ], suggesting that DDX21 may play an important role in the tumorigenesis of CRC. We also validated the pro-proliferation effect of DDX21 in CRC (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DDX21 was highly expressed in human CRC (37)(38)(39)(132)(133)(134). Its expression was associated with CRC cancer stages (133).…”
Section: Ddx21mentioning
confidence: 99%